Cardiovascular risk factors, radiation therapy, and myocardial infarction among lymphoma survivors. (2nd September 2022) - Salz, Talya; Zabor, Emily C.; Brown, Peter De Nully; Dalton, Susanne Oksbjerg; Raghunathan, Nirupa J.; Matasar, Matthew J.; Steingart, Richard; Hjalgrim, Henrik; Specht, Lena; Vickers, Andrew J.; Oeffinger, Kevin C.; Johansen, Christoffer
Abstract: Background: Mediastinal radiation is associated with increased risk of myocardial infarction (MI) among non-Hodgkin lymphoma (NHL) survivors. Objective: To evaluate how preexisting cardiovascular risk factors (CVRFs) modify the association of mediastinal radiation and MI among a national population of NHL survivors with a range of CVRFs. Material and methods: Using Danish registries, we identified adults diagnosed with lymphoma 2000–2010. We assessed MI from one year after diagnosis through 2016. We ascertained CVRFs (hypertension, dyslipidemia, and diabetes), vascular disease, and intrinsic heart disease prevalent at lymphoma diagnosis. We used multivariable Cox regression to test the interaction between preexisting CVRFs and receipt of mediastinal radiation on subsequent MI. Results: Among 3151 NHL survivors (median age 63, median follow-up 6.5 years), 96 were diagnosed with MI. Before lymphoma, 32% of survivors had ≥1 CVRF. 8.5% of survivors received mediastinal radiation. In multivariable analysis, we found that mediastinal radiation (HR = 1.96; 95% CI = 1.09–3.52), and presence of ≥1 CVRF (HR = 2.71; 95% CI = 1.77–4.15) were associated with an increased risk of MI. Although there was no interaction on the relative scale ( p = 0.14), we saw a clinically relevant absolute increase in risk for patients with CVRF from 10-year of MI of 10.5% without radiation to 29.5% for those undergoing radiation. Conclusion: Patients with CVRFs have an importantly higher risk of subsequent MI if they have mediastinal radiation. Routine evaluation of CVRFs and optimal treatment of preexisting cardiovascular disease should continue after receiving cancer therapy. In patients with CVRFs, mediastinal radiation should only be given if oncologic benefit clearly outweighs cardiovascular harm.